Current Control of the Single-Phase Full-Bridge Power Inverter - Marian Gaiceanu (Analele Universităţii "Eftimie Murgu" Reşiţa: Fascicola I, Inginerie, 2014)
This paper shows the Matlab/Simulink implementation of the current control in a single phase full-bridge power inverter. In order to increase the performances of the power inverter an LC filter is connected at the input. Mathematical modelling of the power inverter is based on the switching functions. Unipolar asymmetric PWM modulation method, and hysteresis current control will be analyzed for a connected RL load to power inverter output. Simulation results based on the Matlab/Simulink® control implementation are shown.